Влияние адреналина на АДФ-индуцированную агрегацию тромбоцитов при хронической ишемии головного мозга = Effect of epinephrine on ADP-induced platelet aggregation at chronic brain ischemia - Barinov, E. F.; Mamedaliyeva, S.; Balykina, A. O.; Tverdokhleb, T. A. (Journal of Education, Health and Sport, 2015)
Barinov E. F., Mamedaliyeva S., Balykina A. O., Tverdokhleb T. A. Влияние адреналина на АДФ-индуцированную агрегацию тромбоцитов при хронической ишемии головного мозга = Effect of epinephrine on ADP-induced platelet aggregation at chronic brain ischemia. Journal of Education, Health and Sport. 2015;5(6):11-18. ISSN 2391-8306. DOI 10.5281/zenodo.18191 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A11-18 https://pbn.nauka.gov.pl/works/562793 http://dx.doi.org/10.5281/zenodo.18191 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.05.2015. Revised 28.05.2015. Accepted: 31.05.2015. ВЛИЯНИЕ АДРЕНАЛИНА НА АДФ-ИНДУЦИРОВАННУЮ АГРЕГАЦИЮ ТРОМБОЦИТОВ ПРИ ХРОНИЧЕСКОЙ ИШЕМИИ ГОЛОВНОГО МОЗГА EFFECT OF EPINEPHRINE ON ADP-INDUCED PLATELET AGGREGATION AT CHRONIC BRAIN ISCHEMIA Э. Ф. Баринов, Севиндж Мамедалиева, А. О. Балыкина, Т. А. Твердохлеб E. F. Barinov, Sevyndzh Mamedaliyeva, A. O.Balykina, T. A. Tverdokhleb Донецкий национальный медицинский университет им. М. Горького Donetsk National Medical University Abstract Determination of the mechanisms of platelets adaptation against the action of exogenous signals will expand tactics of pharmacological correction aimed at thrombogenesis prevention. The purpose of the studies to establish in vitro modulating effect of epinephrine on platelet aggregation induced by ADP. We used platelet-rich plasma, which was isolated from the blood of 55 patients with a diagnosis of chronic cerebral ischemia(CCI) of stage 1-2. Study was carried out on the aggregometer Chrono - Log (USA). Modulatory role of subthreshold epinephrine doses in platelet activation was analyzed by it addition to a suspension of platelets stimulated by ADP (EC50). It is established that: (a) there are differences in the response of platelets to epinephrine at CCI; (b) epinephrine activity effects on functional response of platelets stimulated by ADP; (c) as threshold epinephrine dose can modulate ADP-induced platelet aggregation. Key words: chronic cerebral ischemia, aggregation of the platelets, epinephrine. Реферат Выяснение механизмов адаптации тромбоцитов при действии экзогенных сигналов позволит расширить тактику фармакологической коррекции направленной на профилактику тромбогенеза. Цель исследования - установить in vitro модулирующее влияние адреналина на агрегацию тромбоцитов индуцированную АДФ. Использована обогащенная тромбоцитами плазма, которую выделяли из крови 55 пациентов с диагнозом хронической ишемии головного мозга 1-2-й стадии. Исследование агрегации тромбоцитов проведено на агрегометре фирмы Chrono - Log (США). Модулирующую роль субпороговой дозы адреналина в активации тромбоцитов анализировали при ее добавлении в суспензию тромбоцитов стимулированных АДФ (ЕС50). Установлено, что: (а) у пациентов с хронической ишемией мозга имеются различия реакции тромбоцитов на адреналин; (б) адренореактивность влияет на функциональный ответ тромбоцитов при их стимуляции АДФ; (в) субпороговая доза адреналина может модулировать АДФ-индуцированную агрегацию тромбоцитов. Ключевые слова: хроническая ишемия головного мезга, агрегация тромбоцитов, адреналин.